Risiko Kejadian Pnemonia pada Balita Kaitannya dengan Tipe Rumah di Wilayah Kerja Puskesmas Sidorejo Lor dan Cebongan Kota Salatiga. - Zuraidah, Siti; Adi, Sakundarno; Udiyono, Ari (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2002)
ABSTRACT Background : In Indonesia, pneumonia is quantitatively the biggest problem among infectious diseases of infants. Based on the World Health Organization data, incidence of pneumonia among children under five years old in Indonesia is 10%.. Pneumonia detection rate in Salatiga in the year of 2001 is still low (6%). The causes of this low detection rate are lack of trained health workers in the management of Acute Respiratory Infection (ARI) in the primary health center level and lack of â€œari timerâ€ usage by the health workers to classify pneumonia patients. Objectives of this study are to know the risk of getting pneumonia among children under five year old who live in the non permanent house. Methods : this was a cohort study, independent variable of interest was house type. Other independent variables was nutritional status, immunization status, sex, duration of breast feeding, infant age, ventilation, type of energy for cooking, house occupant density, motherâ€™s education, motherâ€™s age and type of the floor. Samples consistedÂ of 208 children under five year old who were suffering from ARI. Of those samples, 104 children were living in the permanent houses (unexposed group) and other 104 children were living in the non permanent houses (exposed group). Analysis were conducted by calculating Relative Risk (RR) and by applying multiple logistic regression. Result : the study shows that pneumonia occur in 31,25%Â of the samples. Crude Relative Risk (c-RR) for the exposed group compared to the unexposed group is 4. This RR varies between 5,440 and 7,8248 after stratifying association between house type and the occurrence of pneumonia with other independent variables. Risk factor of pneumonia among children under five year old are non permanent house (p=0,001; OR=5,0341); bad ventilation (p=0,0001; OR=21,108) and wood of energy for cooking (p=0,0066; OR=3,115). Conclusion : : Non permanent house, bad ventilation and stick of energy for cooking, are to be risk factors of pneumonia among children under five year old in the working area of Sidorejo Lor and Cebongan Primary Health Centers. It is suggested primary health centers and the linked institution do together for health education, house improvement and not use wood of energy for cooking. Key Word : pneumonia, children under five year old, house type.